2024
DOI: 10.1177/20563051231224401
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic Ventriloquism: The Contested State of Voice in AI Speech Generators

Ido Ramati

Abstract: This article explores the vocal human–machine relations embedded in text-to-speech (TTS) generators. Retracing the human sources behind the synthetic speech and tracking the remediation of the voice by the machine-learning algorithm, it argues that artificial intelligence (AI) speaking agents such as Siri and Alexa, as well as other TTS acts such as TikTok’s, are performing algorithmic ventriloquism. Speaking mechanically with the voices of professional voiceover artists, AI speech technologies algorithmically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Pretend play involves the children to play mock by following an impromptu path where ventriloquism is used to speak objects in life through paralinguistic features such as movement gestures, gazes and sounds. These findings indicated that through ventriloquism action in mock plays, the children learn to engage in the complex meaning of making activities in fun ways, formulating oral characters and building a coherent and systematic storyline that can be identified as early literacy practices (Ramati, 2024). Most of the teachers make pretend play stories with medical themes, but the children are less influential as well as less fantasy and comfortable during the play.…”
Section: Introductionmentioning
confidence: 97%
“…Pretend play involves the children to play mock by following an impromptu path where ventriloquism is used to speak objects in life through paralinguistic features such as movement gestures, gazes and sounds. These findings indicated that through ventriloquism action in mock plays, the children learn to engage in the complex meaning of making activities in fun ways, formulating oral characters and building a coherent and systematic storyline that can be identified as early literacy practices (Ramati, 2024). Most of the teachers make pretend play stories with medical themes, but the children are less influential as well as less fantasy and comfortable during the play.…”
Section: Introductionmentioning
confidence: 97%